Analysis of Operation Damai Cartenz Planning in the Management of Armed Criminal Group Mitigation in Papua - Librian, Andre; Setyabudi, Chairul Muriman; S., Basir (CV. Proaksara Global Transeduka, 2026)
Cartenz Peace Operation is a continuation of the Papua Task Force (2016) and Operation Nemangkawi (2018). The existence of Operation Cartenz Peace indicates a rapid shift in nomenclature. However, an in-depth analysis of its formation process reveals critical gaps in standard police operational procedures. There has been no in-depth study or planning conducted prior to each name or strategy change. In fact, a successful operation must be based on careful planning that begins with a comprehensive study. The study intends to examine the planning issues of the Cartenz Peace Operation and suggest reclassifying it as an Enhanced Routine Activity (KRYD) for better management of armed criminal groups in Papua. The research method used is qualitative-descriptive. The approach used in this study is a case study. Operation Cartenz Peace was chosen as a unique and specific case for in-depth analysis. The analysis will focus on the planning process, decision-making, policy implementation, and evaluation of the results of this operation. The results and discussion reveal that Operation Cartenz Peace did not meet the criteria for a police operation. Operation Cartenz Peace should be reclassified as an Enhanced Routine Activity (KRYD). This classification denotes activities conducted by regional units with increased personnel and budget allocations, without the rigid time limitations that characterize formal operations.